CRIMINOLOGICAL ANALYSIS OF INDICATORS OF MEASUREMENT OF CRIMINAL OFFENSES AGAINST TRAFFIC SAFETY AND TRANSPORT OPERATION IN UKRAINE - Novikov, Oleg (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: analysis of the current state and trends of criminal offenses against traffic safety and transport operation in Ukraine on the basis of official statistics. The methodological basis were both general scientific and specific statistical methods of cognition (in particular: statistical observation, compilation and grouping of data, absolute and relative indicators, tabular and graphical methods, etc.). Results: in 2020, 15,795 criminal offenses against traffic safety and transport operation were recorded, 6,042 perpetrators were identified, and 3,127 individuals were convicted of these criminal offenses (almost every second of those identified is convicted). Criminal offenses against traffic safety and transport operation average 4.03% of the crime structure in Ukraine and rank 6th in prevalence in the country. Among these offenses, the most committed are: violation of traffic safety rules or operation of transport by persons driving vehicles (Article 286 of the Criminal Code of Ukraine), illegal possession of a vehicle (Article 289 of the Criminal Code of Ukraine) and destruction, forgery or replacement of numbers of units and units means (Article 290 of the Criminal Code of Ukraine). The nature of the criminal offenses investigated is 36%, i.e. slightly more than every third criminal offense against traffic safety and transport operation is serious or particularly serious. Almost 70% of these criminal offenses are crimes and 30% are criminal offenses. The largest number of criminal offenses against traffic safety and transport operation is found in Kyiv, Dnipropetrovsk, Odesa, Kharkiv, Kyiv and Lviv oblasts, and the smallest in Luhansk, Chernihiv, Ternopil, Kirovohrad and Khmelnytsky oblasts. For the last 5 years the negative dynamics of the investigated criminal offenses is fixed. Discussion: the author emphasizes the need for criminological research on the latency of criminal offenses against traffic safety and transport operation.